2020
DOI: 10.1186/s11671-020-03438-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanotechnology in Wood-Based Products Industry: A Review

Abstract: Wood-based industry is one of the main drivers of economic growth in Malaysia. Forest being the source of various lignocellulosic materials has many untapped potentials that could be exploited to produce sustainable and biodegradable nanosized material that possesses very interesting features for use in wood-based industry itself or across many different application fields. Wood-based products sector could also utilise various readily available nanomaterials to enhance the performance of existing products or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 284 publications
(297 reference statements)
0
11
0
Order By: Relevance
“…Besides, the 1D fibrous cellulose has also been extracted and widely applied as templates, building blocks, separators, and hosts for electrode materials to fabricate flexible electrochemical energy storage devices, where they were usually integrated with active materials. [ 7,20 ]…”
Section: Electrochemical Energy Storage Devicesmentioning
confidence: 99%
“…Besides, the 1D fibrous cellulose has also been extracted and widely applied as templates, building blocks, separators, and hosts for electrode materials to fabricate flexible electrochemical energy storage devices, where they were usually integrated with active materials. [ 7,20 ]…”
Section: Electrochemical Energy Storage Devicesmentioning
confidence: 99%
“…They also reported that the average particle size of copper used in the treatments was 16.5 nm. It has been reported in the literature that there is an advantage in the use of nanoproducts in wood impregnation, given their ability to enter deeply into the wood structure, hence improving the penetration and retention of the nanoparticle solution used as a preservative [41,42].…”
Section: Retention and Leachability Of Cunps In Radiata Pine Woodmentioning
confidence: 99%
“…Nanotechnology can be used to form a very hard clear coating on a wood surface [ 59 , 60 ]. Nanotechnology is defined as the manipulation of matters between 1 and 100 nm.…”
Section: Property and Modificationmentioning
confidence: 99%
“…Figure 17A shows a surface coating failure due to moisture sorption and Figure 17B shows a coating failure due to end grain moisture sorption [56]. Nanotechnology can be used to form a very hard clear coating on a wood surface [59,60]. Nanotechnology is defined as the manipulation of matters between 1 and 100 nm.…”
Section: Coatingsmentioning
confidence: 99%